PRAANGGAPAN PADA BAHASA SPANDUK DEMO "ORANG MISKIN DILARANG SARJANA" DI MEDIA SOSIAL (KAJIAN PRAGMATIK) - Fajrin, Muhammad; Tenri Sua, Andi; Suhardiman (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
This study aims to describe the forms of presuppositions in the language of the demonstration banner "Poor People Are Prohibited from Having Graduates" and to identify the types of presuppositions in public comments on social media. This study uses a qualitative method with a case study approach and a qualitative descriptive design. Data were analyzed based on George Yule's theory of presuppositions, which includes six types: existential, factual, nonfactual, lexical, structural, and counterfactual presuppositions. The results of the analysis show that the speech in the banner and public comments contain various forms of presuppositions that reflect social criticism, satire, and the reality of educational inequality. These findings are expected to enrich pragmatic studies, especially in the analysis of social criticism discourse in the digital era.